La motivación y su influencia en el desempeño del personal operativo de la Empresa Cnel. Los Ríos - Barahona Adrihan, Gina Patricia (2017)
The company CNEL the rivers are dedicated to the provision, commercialization and distribution of electric energy throughout the country, began its activity on December 15, 2008 by public deed where the companies of different provinces worked, this is based on the need for humanity, because electric energy is a basic service essential for the home, industry and commerce worldwide, this service is indispensable for the satisfaction of human beings in the different activities they perform